Comprar para revender: Un encargo del agente comercial (2018)
"The commercial agency, as a distribution contract, raises debates between the legal operators that resolve contractual disputes and the academic community. In this sense, this article aims to answer one of the biggest questions surrounding the agency: who buys to resell is a commercial agent? Thus, through the systematization of debates and the construction of own arguments, we will defend the idea that the activity of buying to resell does not denature the agency contract in Colombian law." -- Tomado del Formato de Documento de Grado